The Relationship among Self-efficacy, Metacognitive Ability and Academic Motivation with Math Performance of High School Students in Parsian - Movaghar, Mahnaz; Darman, Fariba; Gholami, Mohammad Hosein (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to determine the relationship among self-efficacy,meta-cognitive ability and academic motivation with math performance of highschool students in Parsian. This research has been applied in a purposeful anddescriptive way and has been correlated with research type. The statisticalpopulation of this study was all high school students in Parsian. Sample size: 150people were selected by cluster sampling method. Measurement tools were selfefficacyquestionnaire, meta-cognitive ability questionnaire and academicmotivation questionnaire. The results of this research have shown that there is asignificant and positive relationship between self-efficacy, metacognitive ability,academic motivation and mathematical function. Also, student's math performanceis predictable through the components of self-efficacy, metacognitive ability, andacademic motivation. In total, approximately 30.3% of variance predicts students'mathematical performance variables.